Technical fitness of judoists (weight category -66 kg) participating in European Championships 2005 - Kruszewski, A.; Jagiello, W.; Adamiec, T. (Physical Education and Sport, 2008)
To assess the degree of technical preparation of judoists from -66 kg category participating in European Championships 2005 and to identify the factors associated with winning medals. Material and methods: The performance of judoists was assessed from video recordings and described by applying indices of combat activity, efficacy and score ratios. Results: Throws, and especially hand throws (te-waza) were the dominating techniques but the hip throws (koshi-waza) proved most effective. Conclusions: When preparing for top competitions, improving the te-waza and sutemiwaza throws, as well the defence against throws from nage-waza category ought to be emphasised.